The non-discrimination principle and personal data protection in the context of the EU digital COVID certificate - Koukiadis , Dimitrios I. (Lex Social: Revista de Derechos Sociales, 2022)
The measures adopted so far, on EU Members-States level, aiming at containing Covid-19 have, very often, demonstrated an extremely fragmented, un-coordinated and controversial policy-making process. On July 1st, 2021, the EU Digital Covid Certificate entered into application throughout the EU seeking to provide for a common, harmonized, common legal framework in order to protect public health, re-open the borders, re-activate European economy, and facilitate the free movement of individuals during pandemic through establishing secure, verifiable, and interoperable measures across the EU territory. Issues of non-discrimination and equality, freedom of movement, working conditions, data protection, asylum and migration, human dignity, the rule of law, and the overall respect for human rights have been raised.